The Role of Human Development and Decentralization toward Poverty Through Economic Growth - Jihad Lukis Panjawa; Joko Triyanto (Gorontalo Development Review, 2020)
Efforts to reduce poverty that continue in the sustainable development goals (SDGs), need to research with different approaches for each different problem. The objective of this research is to analyze the direct and indirect effects of human development and fiscal decentralization on poverty through economic growth in eastern Indonesia. The analytical method used the causal model for directly observed variables. The results show that there is no significant effect on human development and fiscal decentralization on economic growth. In addition, human development has negative and significant direct effect on poverty but does not affect poverty through economic growth. Fiscal decentralization has no effect on poverty through economic growth, while economic growth has negative and significant direct effect on poverty. Policy by prioritizing improving human resource qualities will be effective in reducing poverty directly.